PEMBERDAYAAN BERFIKIR KRITIS SISWA MELALUI MODEL SQ3R (survey, question, read, review, recite) DENGAN MEDIA AUDIO VISUAL DITINJAU DARI GAYA KOGNITIF REFLEKTIF DAN IMPULSIF - Ananda Kenang Nur Aida; Imas Cintamulya (Biogenesis, 2018)
ABSTRACT So far, the teacher's learning is mostly presented with lecture method and only centered on the teacher, it causes the critical thinking of the students is still very rare in the learning process, besides critical thinking other thing to note is student's cognitive style.Therefore it is necessary to do research about the empowerment of critical thinking in terms of reflective and impulsive cognitive style. The purpose of this study is to describe the ability of critical thinking students reflective and impulsive cognitive style through SQ3R learning model (survey, question, read, review, recite) by using Audio Visual media. The subjects of the study were students of class VII-B MTs. Muhammadiyah 3 Sedayulawas amounted to 20 students consisting of 10 students of reflective cognitive style and 10 students of cognitive impulsive style. Technique of collecting data by using test, for data koSo far, the teacher's learning is mostly presented with lecture method and only centered on the teacher, it causes the critical thinking thinking of the students is still very rare in the learning process, besides critical thinking other Thing to note is student's cognitive style. Statistically non-parametric by using Mann-Whitney Test.The results of this study indicate that there are differences in reflective and impulsive students' critical ways of thinking ie impulsive students show higher results from reflective students. Thus it can be concluded that the critical thinking ability of cognitive-impulsive students is higher than in reflective cognitive students in Biology learning through SQ3R model (survey, question, read, review, recite) with Audio Visual media. Keywords: Critical Thinking, Reflective Cognitive and Impulsive, SQ3R, Audio Visual